Stereoselective syntheses of (+)-alpha- and (-)-beta-conhydrine from L-aspartic acid - Pandey, SK; Kumar, P (Tetrahedron Letters, 2005)
An efficient synthesis of (+)-alpha-conhydrine 1 and (-)-beta-conhydrine 2 has been achieved by. diastereo selective alkylation of an amino aldehyde derivative 7 with ethylmagnesium bromide or diethylzinc. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Alkylation; conhydrine; Grignard reaction; Piperidine alkaloids; stereoselectivity